Dialektika Pendidikan Akhlak Era 5.0: Studi Analisis Pemikiran Ibnu Miskawaih - Sabililhaq, Irhas; Awaluddin, Raisa Zuhra Salsabila; Nida, Sofwatun (DIMAR: Jurnal Pendidikan Islam, 2025)
The issue of moral decline in the generation of the nation post-globalization, with its various life implications, calls for the development of an adaptive and inclusive concept in the field of education. This study aims to explore Ibn Miskawaih's ideas and their relevance in the context of Education 5.0. It is a qualitative study that uses a library research method, with primary sources including a book by Ibn Miskawaih and secondary sources consisting of various journal articles. Data were gathered from a range of books and articles, then analyzed through content analysis techniques. The findings indicate that Ibn Miskawaih, a prominent Islamic philosopher of the Buwayhi Dynasty during the Abbasid era, contributed significantly to the philosophy of human beings. He believed that humans consist of two essential components: the physical body and the soul, both of which are interconnected in shaping a 'wholesome human' with good morals. Ibn Miskawaih's ideas remain relevant to modern Islamic education, aligning with the educational goals outlined in the National Education System Law (UU Sidiknas) Article 1 of 2003. He argued that moral education should be rooted in the doctrine of moderation and carried out through habituation, where repeated actions eventually shape a child’s or learner’s character. Therefore, every individual has the potential to develop good morals through proper education and guidance.